Brand identity canvas: a framework to bring clarity and relevance to brands - ALVES, Antonio Pedro Cruz Costa (2022)
This master’sthesis presents a new brand identity model for consumer goods called Brand Identity Canvas (BIC), with the objective of helping academics and practitioners build more relevant and stronger brands. Our work updates the current and most influential brand identity models theorised mainly in the 1990s, including components and discussing interactions not previously addressed by scholars. We adopted the Design Science Research methodology, which is adequate for building artefacts and theoretical frameworks. The framework development was based on a literature review and 11 in depth interviews with practitioners (marketing managers and directors) and academics (marketing and branding professors). The new model has two parts: the first is managerial, with a description of the intrinsic characteristics of the brand and its influences; the second is expressive, with a mood board that explores the brand’s visual aspects. The BIC presents academics and practitioners with an updated framework for defining and developing a brand identity for consumer goods, with dimensions, components, and relations representing an advance on the existing models.